Investment Criteria, Productivity and Economic Development: Reinterpretation - Kilby, Peter (Quarterly Journal of Economics, 1964)
Journal Article Investment Criteria, Productivity and Economic Development: Reinterpretation Get access Peter Kilby Peter Kilby St. Antony's College, Oxford Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 78, Issue 3, August 1964, Pages 488–495, https://doi.org/10.2307/1879481 Published: 01 August 1964